Helicenes with Embedded Phosphole Units in Enantioselective Gold Catalysis1. (6th December 2013) - Yavari, Keihann; Aillard, Paul; Zhang, Yang; Nuter, Frédérick; Retailleau, Pascal; Voituriez, Arnaud; Marinetti, Angela
Abstract This paper discloses the first uses of phosphahelicenes as chiral ligands in transition‐metal catalysis. Unlike all known helical phosphines used so far in catalysis, the phosphorus function of phosphahelicenes is embedded in the helical structure itself. This crucial structural feature originates unprecedented catalytic behaviors and efficiency. An appropriate design and fine tuning allowed both high catalytic activity and good enantiomeric excesses to be attained in the gold promoted cycloisomerizations of N‐tethered 1, 6‐enynes and dien‐ynes.